Impact of non-compliance on financial performance: a case study of the National Social Security Authority(NSSA), 2009-2013 - Rwafa, Livingstone T. (Midlands State University, 2015)
This study sought to determine the impact of non-compliance on statutory obligations by employers to the financial performance of NSSA. In this study 20 employers, 10 inspectors and 3 Principal compliance inspectors and the Compliance Manager were used as research subjects. The researcher used questionnaires and interviews as research instruments. The study showed that the main causes of non-compliance by employers to their statutory obligations taking social security contributions to the National Social Security Authority as a case study are; financial constraints that were caused by the harsh economic environment, Low pension benefits that are paid by NSSA, high contribution rates and to some extent complexity of calculations. Non-compliance was found to be impacting negatively to the financial performance of NSSA as indicated by the deteriorating operating revenues and profits as well as delays in payment of NSSA pensions. This study recommends that to reduce non-compliance by employers NSSA need to improve on debt recovery strategies like payment plans negotiation and prosecution, carrying outeducational campaigns, increase the number of inspectors, increasing pension benefits so that employers are motivated to comply and simplifying calculation of monthly dues so that employers do not have to wait for inspectors for them to make payments. Related to this is also considering convenient payment methods such as Eco-cash. Finally it is also recommended that further research be undertaken in order to assess the impact of non-compliance on financial performance of NSSA and other statutory obligations when the economic environment normalises as this research was done when Zimbabwe was facing difficult macro-economic conditions. The same study may also be extended to other regions as this research focused on Harare only.